Mast Cell Chymase/Mcpt4 Suppresses the Host Immune Response to Plasmodium yoelii, Limits Malaria-Associated Disruption of Intestinal Barrier Integrity and Reduces Parasite Transmission to Anopheles stephensi - Céspedes, Nora; Donnelly, Erinn L.; Lowder, Casey; Hansten, Gretchen; Wagers, Delaney; Briggs, Anna M.; Schauer, Joseph; Haapanen, Lori; Åbrink, Magnus; Van de Water, Judy; Luckhart, Shirley (Frontiers in Immunology, 2022)
An increase in mast cells (MCs) and MCs mediators has been observed in malaria-associated bacteremia, however, the role of these granulocytes in malarial immunity is poorly understood. Herein, we studied the role of mouse MC protease (Mcpt) 4, an ortholog of human MC chymase, in malaria-induced bacteremia using Mcpt4 knockout (Mcpt4-/-) mice and Mcpt4+/+ C57BL/6J controls, and the non-lethal mouse parasite Plasmodium yoelii yoelii 17XNL. Significantly lower parasitemia was observed in Mcpt4-/- mice compared with Mcpt4+/+ controls by day 10 post infection (PI). Although bacterial 16S DNA levels in blood were not different between groups, increased intestinal permeability to FITC-dextran and altered ileal adherens junction E-cadherin were observed in Mcpt4-/- mice. Relative to infected Mcpt4+/+ mice, ileal MC accumulation in Mcpt4-/- mice occurred two days earlier and IgE levels were higher by days 8-10 PI. Increased levels of circulating myeloperoxidase were observed at 6 and 10 days PI in Mcpt4+/+ but not Mcpt4-/- mice, affirming a role for neutrophil activation that was not predictive of parasitemia or bacterial 16S copies in blood. In contrast, early increased plasma levels of TNF-α, IL-12p40 and IL-3 were observed in Mcpt4-/- mice, while levels of IL-2, IL-10 and MIP1β (CCL4) were increased over the same period in Mcpt4+/+ mice, suggesting that the host response to infection was skewed toward a type-1 immune response in Mcpt4-/- mice and type-2 response in Mcpt4+/+ mice. Spearman analysis revealed an early (day 4 PI) correlation of Mcpt4-/- parasitemia with TNF-α and IFN-γ, inflammatory cytokines known for their roles in pathogen clearance, a pattern that was observed in Mcpt4+/+ mice much later (day 10 PI). Transmission success of P. y. yoelii 17XNL to Anopheles stephensi was significantly higher from infected Mcpt4-/- mice compared with infected Mcpt4+/+ mice, suggesting that Mcpt4 also impacts transmissibility of sexual stage parasites. Together, these results suggest that early MCs activation and release of Mcpt4 suppresses the host immune response to P. y. yoelii 17XNL, perhaps via degradation of TNF-α and promotion of a type-2 immune response that concordantly protects epithelial barrier integrity, while limiting the systemic response to bacteremia and parasite transmissibility.